Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1177/23259671231151698
|View full text |Cite
|
Sign up to set email alerts
|

Medial Meniscal Extrusion in Patients With Medial Meniscus Root Tears: A Systematic Review and Meta-analysis

Abstract: Background: Medial meniscal extrusion (MME) has received significant interest because of its correlation with medial meniscus root tears (MMRTs), its potential as a diagnostic tool, and its significance in the progression of knee osteoarthritis (OA). Purpose: To (1) evaluate if MMRTs significantly increase MME compared with nonroot tears (NRTs) and no tears and (2) determine the clinical outcomes of increased MME. Study Design: Systematic review; Level of evidence, 4. Methods: Electronic database searches of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In literature the presence of a meniscal lesion is often associated with meniscal extrusion [7,8,23]. Due to the anatomy of the medial meniscus, various lesions are described as more or less responsible for meniscal extrusion [9,11,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In literature the presence of a meniscal lesion is often associated with meniscal extrusion [7,8,23]. Due to the anatomy of the medial meniscus, various lesions are described as more or less responsible for meniscal extrusion [9,11,18].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the anatomy of the medial meniscus, various lesions are described as more or less responsible for meniscal extrusion [ 9 , 11 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The longstanding physiological loading after meniscus root tear increases in the tear gap, leading to meniscal extrusion [23][24][25][26] . Clinical studies indicated that patients with medial meniscus root tears had signi cantly higher meniscus extrusion compared to those without root tears, while patients with knee OA were more likely to have higher meniscus extrusion compared with those without OA [27] . Notably, the presence of meniscal root tear and subsequent meniscal extrusion are recognized as crucial risk factors for the development of knee OA, underscoring the importance of addressing meniscal extrusion to mitigate the risk of OA in patients with meniscal root tears [28] .…”
Section: Discussionmentioning
confidence: 99%
“…A medial meniscus posterior root tear (MMPRT) is an injury to the posterior meniscal attachment of the tibia that causes abnormal knee joint kinematics. MMPRTs disrupt the hoop function and cause medial meniscus extrusion (MME) [9,25,31,34]. Conservative treatment of MMPRTs is not always efective, and meniscal repair is more efective than both partial meniscectomy and conservative treatment [4,21,22,24].…”
Section: Introductionmentioning
confidence: 99%